LEARNING STRATEGIES USED BY THE FIFTH SEMESTER STUDENTS TO INCREASE THEIR SPEAKING PROFICIENCY AT ENGLISH STUDY PROGRAM IN JAMBI UNIVERSITY - HERYANTI HAZAIRIN (JAMBI-ENGLISH LANGUAGE TEACHING, 2017)
The purpose of this study was to discover the learning strategies that the students of English study program used to increase their speaking proficiency. This study involved six selected students at English study program who were studying in the fifth semester as the participants. They were selected based on their speaking achievement, it was getting scores “A” for three semesters in speaking class. The data were collected from interview with the participants. The study had found out that these students used many learning strategies frequently. In particular, cognitive strategies were found as the most frequently strategies used by the students, followed by metacognitive strategies, interpersonal strategies, affective strategies, social strategies and communicative – experiential strategies.